2010
DOI: 10.1051/0004-6361/200913275
|View full text |Cite
|
Sign up to set email alerts
|

Trend of photospheric magnetic helicity flux in active regions generating halo coronal mass ejections

Abstract: Context. Coronal mass ejections (CMEs) are very energetic events (∼10 32 erg) initiated in the solar atmosphere, resulting in the expulsion of magnetized plasma clouds that propagate into interplanetary space. It has been proposed that CMEs can play an important role in shedding magnetic helicity, avoiding its endless accumulation in the corona. Aims. The aim of this work is to investigate the behavior of magnetic helicity accumulation in sites where the initiation of CMEs occurred to determine whether and how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 38 publications
8
40
0
Order By: Relevance
“…7d). This behavior agrees with the results obtained by Smyrli et al (2010), who analyzed the trend of magnetic helicity accumulation in active regions hosting halo CMEs and found that, in the sample analyzed, the CME events associated with X-class flares display an abrupt change in magnetic helicity at the time of the flare occurrence. In this respect, we recall that Park et al (2008) carried out a statistical study to investigate the variation in magnetic helicity over several days around the times of 11 X-class flares.…”
Section: Magnetic Field Evolutionsupporting
confidence: 91%
See 1 more Smart Citation
“…7d). This behavior agrees with the results obtained by Smyrli et al (2010), who analyzed the trend of magnetic helicity accumulation in active regions hosting halo CMEs and found that, in the sample analyzed, the CME events associated with X-class flares display an abrupt change in magnetic helicity at the time of the flare occurrence. In this respect, we recall that Park et al (2008) carried out a statistical study to investigate the variation in magnetic helicity over several days around the times of 11 X-class flares.…”
Section: Magnetic Field Evolutionsupporting
confidence: 91%
“…We note that the change in the magnetic helicity flux observed after the flare, was probably due to the restoring of the torque balance between the coronal field and the subphotospheric portion of the flux tubes, once the two CMEs were ejected (see Smyrli et al 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Owing to the difficulties encountered when directly measuring the magnetic helicity in the solar atmosphere, usually the authors measure the magnetic helicity transported across the photosphere by the emergence of new magnetic flux or by the shuffling horizontal motion of field lines (see Démoulin 2007, for a review). Several authors have tried to find a temporal correlation between the magnetic helicity variations and eruptive events (Moon et al 2002;Nindos et al 2003;Romano et al 2005;Zhang et al 2008;Smyrli et al 2010). In this context, we recall Hartkorn & Wang (2004) pointing out that the impulsive input of helicity observed during flares might be only an artificial effect of the impact of particle beams, which modifies the spectral line used by the magnetographs.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, many authors have studied the magnetic helicity variations in active regions where solar eruptions took place (Moon et al 2002;Nindos et al 2003;Romano et al 2005;Zhang et al 2009;Smyrli et al 2010). Indeed, the magnetic helicity provides a measure of the global complexity of the magnetic field in an active region, i.e., a measure of the writhe and twist of the magnetic flux tubes, whose interaction favors processes of magnetic reconnection and the consequent release of free magnetic energy.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the above mentioned relationship between the solar eruptions and the magnetic helicity variations, Smyrli et al (2010) applied this method to MDI/SOHO line-of-sight magnetogram data to calculate the magnetic helicity trend in 10 active regions that gave rise to halo coronal mass ejections (CMEs). The results obtained from the sample of analyzed events indicate that the changes in magnetic helicity flux following the CMEs could be attributed to a process of restoring a torque balance between the subphotospheric and the coronal domain of the flux tubes.…”
Section: Introductionmentioning
confidence: 99%